METHODOLOGY FOR PROCESSING THE RESULTS OF CHANGES IN TECHNOLOGICAL PARAMETERS OF DRILLING COMPLETED OIL AND GAS WELLS - Moisyshyn, V. M.; Ivasiutyn, A. P.; Tyrlych, V. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
Modern drilling rigs, such as the Ultra Single 150 drilling complex developed by the Canadian company Sense EDM, are equipped with control and measuring instruments. The monitors are located in the drilling master's control room. Their use allows for recording discrete values of all technological parameters of the drilling process with a sampling step of 1 m of well depth. These values are stored for completed oil and gas wells in the appropriate data bank on electronic media. Fixing changes in drilling technological parameters allows for analyzing the impact of using modern technologies on the rock destruction process. To conduct such an analysis, it is necessary to select homogeneous areas of well deepening according to the accepted drilling criterion, for example, according to the change in mechanical drilling speed. The authors have developed a method for processing the results of changes in technological drilling parameters of completed wells. The program App.2 is proposed for determining homogeneous borehole sections of the well, which is developed in the Visual Studio software environment in the C# programming language (C Sharp) using the Windows Form Application framework using Windows operating systems. The peculiarity of this technique is that for homogeneous drillability sections of the deepening, the distribution law and statistical characteristics are determined for the main technological parameters, which include the mechanical drilling speed (drillability criterion), axial static load on the bit, the torque of the installation rotor, and the rotation speeds of the rotor and bit. Belonging homogeneous well-depth sections to one general population is determined by the testing results statistical parametric hypotheses for all the above technological parameters. If at least one parametric hypothesis about the equality of variances and mean values of the compared samples of discrete values of these parameters is rejected, the hypothesis about the belonging homogeneous linear sections to the well interval with the same physical and mechanical characteristics of the rock is rejected.